Analisis Variasi Spasial Harga Tanah pada Area terdampak Pembangunan Tol Akses Balikpapan - Ibu Kota Nusantara menggunakan Metode Inverse Distance Weighted (IDW) - Fajri, Fadel Ghulam; Septanaya , I Made Dewa Frendika; Susetyo , Cahyono (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to analyze the spatial variation in land prices in areas affected by the construction of the Balikpapan–IKN Access Toll Road using the Inverse Distance Weighted (IDW) method. Land price data were obtained through field observations at 325 sample points over two observation periods: pre-construction (2017) and post-construction projection (2025). This research uses the Inverse Distance Weighted (IDW) interpolation approach. Data processing was carried out using ArcGIS and the IDW interpolation technique, which considers the influence of distance between points by assigning weights inversely proportional to the distance. The results of the study show a significant increase in land prices, with some points experiencing increases of up to 481% and an average increase of approximately 261%. Spatial analysis through interpolated maps revealed that proximity to key infrastructure, such as toll roads and arterial roads, contributed to an increase in market value. These findings provide a comprehensive overview of the impact of infrastructure development on land price dynamics and offer valuable insights for urban planning and regional development policies. The study also proposes strategic recommendations for policymakers to enhance planning and regional development based on the spatial analysis results.